"Sexo y represión en el período colonial en la Alcaldía Mayor de Tegucigalpa" - Aquiles Valladares, Omar (2016)
In Honduran historiography, studies on sexuality, until a few years ago, were taboo topics, or at least not frequent ones. They are almost inexistent in research on the Honduran colonial period. The present article tries to open new possibilities of research; the primary objective is to investigate the documentation about sexual crimes, their definition, and the application of penalties. This article focuses on incest, homosexuality, and cohabitation; how abuse and discrimination against women is revealed in these cases; and the masculine discourse that has favored the notion that woman is the source of sin, an evil that provokes men to fall into the abyss of lust.